Pengaruh Product Quality Terhadap Purchase Decision Yang Dimediasi Oleh Customer Experience Dan Brand Trust Pada Produk Skintific - Rizky, Fifi Dea; Roosdhani, Mohamad Rifqy (Universitas Islam Kadiri, 2025)
This research aims to examine the impact of product quality on purchasing decisions, with customer experience and brand trust acting as mediating variables in Skintific products. Data was gathered through online questionnaires completed by 119 respondents who are users of the product. The study employed validity and reliability tests, along with analysis using SmartPLS 4.0 software to evaluate the model and test hypotheses. The findings indicate that product quality significantly influences customer experience in a positive way. Additionally, product quality has a notable positive impact on brand trust. Moreover, customer experience plays a significant role in enhancing purchase decisions, while brand trust also positively affects purchase decisions. Furthermore, product quality itself has a direct and significant effect on purchase decisions. Mediation analysis confirms that both customer experience and brand trust effectively bridge the relationship between product quality and purchasing decisions. These results suggest that enhancing product quality can strengthen customer experience and brand trust, ultimately leading to higher purchase decision.